Study of hematology according to the morphology classification and Some Biochemical Values Changes Associated With Morphological Anemia - Ali H. AL-jaumeili (Tikrit Journal of Pure Science, 2023)
This study was conducted on sheep to determine the changes in hematological and biochemical parameters in anemic cases by using morphological classification, one hundred and thirty serum samples were collected sheep aged 1 – 5 years, they were grazing on pasture from the different districts of Tikrit. which was a sample of 100 sheep suffered from anemia and 30 sample was intact. The results showed that the sheep's which suffer from anemia, a significant decrease in  RBC count, Hb concentration, PCV, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration in normocytic normochromic ( 0.3±6.5 × 106µ/L), (0.49±6.1 g/dl), (0.29±18.6%), (0.33±28.6 fl), (0.72±9.4 pg), (0.61±33.03 g/dl) respectively. In microcytic hypochromic, (0.63±7× 106µ/L) ,( 0.23±6 g/dl) ,( 0.07±18%) ,( 0.34±25.7 fl) ,( 0.04±8.57 pg) (0.89±33.33 g/dl) respectively. But in macrocytic normochromic (0.17±6.3× 106 µ/L)  ,(0.19±7.4 g/dl) , (0.8±22.3%) ,(1.77±34.9 fl) ,(0.67±11.5 pg) (1.11±33.1g/dl) respectively. In macrocytic hypochromic, (0.41±6.7× 106µ/L) , (0.16±7.8 g/dl) ,(0.13±23.5%) ,(1.01±35.1 fl) ,(0.63±11.6 pg) (1.5±33.1 g/dl) respectively. The results showed a significant decrease ( P < 0.05 ) in the rates of total protein concentration , albumin , iron,  copper and zinc (0.16±5.2 g/dl), (0.29±1.16 g/dl), (0.2±117.66 µg/dl), (0.08±42.87 µg/dl), (0.32±39.76 µg/dl)  respectively in the serum of sheep infected according the compared with sheep intact.